2008
DOI: 10.4049/jimmunol.180.8.5569
|View full text |Cite
|
Sign up to set email alerts
|

Down-Modulation of TCR Expression by Salmonella enterica serovar Typhimurium

Abstract: T cell-mediated adaptive immunity is required to help clear infection with the facultative intracellular bacterial pathogen Salmonella enterica serovar Typhimurium (S. Typhimurium), yet development of T cell-mediated adaptive immunity to S. Typhimurium has been described as slow and inefficient. A key step in inducing T cell-mediated adaptive immunity is T cell priming; the activation, proliferation, and differentiation of naive T cells following initial encounter with Ag. We previously demonstrated that S. Ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 68 publications
1
20
0
Order By: Relevance
“…A previous study showed that when Salmonella is in contact with T cells, it decreases TCR expression of both CD4 ϩ and CD8 ϩ cells but does not enhance T-cell apoptosis (34,35). This is consistent with our results suggesting that bacteria may act indirectly through antigen-presenting cells or by the production of cytokines.…”
Section: Discussionsupporting
confidence: 82%
“…A previous study showed that when Salmonella is in contact with T cells, it decreases TCR expression of both CD4 ϩ and CD8 ϩ cells but does not enhance T-cell apoptosis (34,35). This is consistent with our results suggesting that bacteria may act indirectly through antigen-presenting cells or by the production of cytokines.…”
Section: Discussionsupporting
confidence: 82%
“…B. anthracis lethal and edema toxins suppress downstream T-cell signaling through the mitogen-activated protein kinase and calcium signaling pathways, respectively (14,17,42). Salmonella enterica may also express a protein(s) that can down-modulate TCR expression (56). Yersinia pestis produces YopH, a tyrosine phosphatase that can dephosphorylate multiple components of the proximal TCR signaling pathway, including Lck (1), LAT, and SLP-76 (25).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, S. Typhimurium has been found to directly suppress host adaptive immune responses by impeding the actions of specific immune cells; for example, S. Typhimurium induces antigen-presenting cells to adopt distinct migratory paths (Cheminay et al, 2005; Hornef et al, 2002; McLaughlin et al, 2009) and restricts T cell proliferation and activation to limited regions of the body following infection (van der Velden et al, 2005; van der Velden et al, 2008). Other studies have pointed to a more global mechanism for the suppression of adaptive immune responses that involves targeting the draining lymph node, which is the epicenter of the adaptive immune response (St John and Abraham, 2009).…”
Section: Introductionmentioning
confidence: 99%